EMU accession issues in Baltic countries - Raoul Lättemäe (Free University Berlin, Jean Monnet Centre of Excellence, 2003)
After joining EU, the accession countries are expected to join the EMU and the euro-area. This cannot take place immediately after EU enlargement, as prior joining euro-area the accession countries should apply to the European Commission for entering EMU stage three and fulfil Maastricht convergence criteria's. There is no deadline, when accession countries should make the decision to join euro-area. However, there is no opt-out clause for accession countries either, like there was for Denmark and UK in 1999. All accession countries are expected to join the monetary union in some stage. This paper analyses briefly the EMU accession issues in Baltic countries. In addition, a formal inspection of the OCA criteria in Baltic countries is carried out, using the structural VAR methodology. The results of Baltic countries are compared with the results of other accession countries and EU countries.
Keywords: 330